Sympathetic innervation regulates macrophage activity in rat with polycystic ovary - Figueroa, Florencia (2018)
Polycystic ovarian syndrome (PCOS) is a low-grade inflammatory disease characterized by hyperandrogenism and ovarian hyperinnervation. The aim of this work is to investigate whether in vivo bilateral superior ovarian nerve (SON) section in adult rats with estradiol valerate-induced PCOS (PCO rats) affects macrophage spleen cells (MΦ) and modifies the steroidogenic ability of their secretions. Culture media of MΦ from PCO rats and PCO rats with SON section (PCO-SON rats) were used to stimulate in vitro intact ovaries. Compared with macrophages PCO, macrophages from PCO-SON rats released less tumor necrosis factor-a and nitric oxide, expressed lower Bax and Nfkb mRNA and showed reduced TUNEL staining. Also, in PCO rats, the SON section decreased kisspeptin and nerve growth factor mRNA expressions, without changes in Trka receptor mRNA levels. Macrophage secretions from PCO-SON rats decreased androstenedione and stimulated progesterone release in PCO ovaries, compared to macrophage secretions from PCO rats. No changes were observed in ovarian estradiol response. These findings emphasize the importance of the SON in spleen MF, since its manipulation leads to secondary modifications of immunological and neural mediators, which might influence ovarian steroidogenesis. In PCO ovaries, the reduction of androstenedione and the improvement of progesterone release induced by PCO-SON MF secretion, might be beneficial considering the hormonal anomalies characteristic of PCOS. We present functional evidence that modulation of the immune-endocrine function by peripheral sympathetic nervous system might have implications for understanding the pathophysiology of PCOS.